2014
DOI: 10.13005/bbra/1348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sangrovit on Performance and Morphology of Small Intestine and Immune Response of Broilers

Abstract: This study was designed to investigate the effects of Sangrovit on performance, small intestinal morphology, and immune response of 300 commercial hybrid broilers, Ross 308. The study was conducted in the Agricultural Research Station of Islamic Azad University, Varamin, in the spring 2010 for 42 days. The broilers were kept in a completely randomized design with 3 treatments, 4 replicates, 12 experimental units each containing 25 broilers. Treatments used in this experiment included controls, 0.05 % and 0.1 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Our findings were in accordance with those of Karimi et al. (), who showed that the intake of 7.5 mg sanguinarine/kg of diet (500 g Sangrovit/kg) improved the antibody titre in broiler chicks. However, Mirzadeh et al.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were in accordance with those of Karimi et al. (), who showed that the intake of 7.5 mg sanguinarine/kg of diet (500 g Sangrovit/kg) improved the antibody titre in broiler chicks. However, Mirzadeh et al.…”
Section: Discussionsupporting
confidence: 93%
“…Dietary supplementation of quaternary benzophenanthridinze and protopine alkaloids combination has been related to increasing of villi height, villi width, villus/crypt ratio, and surface area of jejunum in broilers [53]. Conversely, Karimi et al [16], and Zhang et al [54], reported that dietary supplementation with sanguinarine had no effect on intestinal histology which is more in line with our data. Comparing ileum photomicrograph of broilers under NE challenge and phytobiotic supplementation represented a slight improvement in villus structure.…”
Section: Discussionsupporting
confidence: 89%
“…In the current trial, the supplementation of sanguinarine-based phytobiotic did not affect performance parameters in the post-NE induced infection period. Others reported an increase in body weight, enhanced performance, and carcass yield [11,16]. Recently El-Sheikh et al [48], reported an improvement in the clinical signs of NE in birds under C. perfringens and sanguinarine phytobiotic supplementation, including intestinal lesion scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ross 308 broilers fed MCEP at 500 and 1000 mg/kg feed (0.05% and 0.1% of the diet, respectively) also did not significantly increase feed intake, FCR or small intestinal morphology during the entire 42 day study period [7]. However, transient increases in LW and cumulative MCEP effects were found [8] when MCEP was consumed at 50 mg/kg feed from D1 -D21 and MCEP at 25 mg/kg feed from D22 -D42 by male Cobb broiler chicks, corresponding to increased feed intake.…”
Section: Discussionmentioning
confidence: 89%